Gênero discursivo seminário : um objeto de ensino - Monteiro, Alexandra Oliveira (2018)
We recognize the school environment as one of those responsible for developing in our students skills that enable them to think and transmit critical and coherent positions about their own community, society and world. And since we are aware of the role that communication plays in achieving this goal, we want our students to know how to express themselves safely, using clear, objective language appropriate to the situation in which they perform the linguistic act. Thus, they will convey credibility to their interlocutors and make them adhere to their opinions. In this sense, the beginning of concrete work for the teaching of the mother tongue must be done through the different genres, because it is through them that we communicate. However, when there is this recognition, emphasis is placed on written genres, so we propose a systematic activity with oral genres, since, even recognizing the importance of the written modality, the literate world has shown us the need for the student to expand his communication potential in social spheres, demonstrating a good communicative performance in the most diverse contexts, so the school should also promote oral language learning in the various situations of use, especially in the more formal ones. Thus, we see the seminar as an important bridge for this work, so our goal was to discuss the insertion of this discursive genre as an object of teaching, in Portuguese language classes, in aclass of 9th grade elementary school in a state school of the city of Aracaju. All stages of preparation to reach an excellent exposition should be considered, therefore, the construction of this activity also requires the importance of the argumentation,since our proposal is that the students should argue their positions on the subject worked and listen to the opinions of others. The seminar can no longer be exposed in a simplified way, only with division of group and subject, it must really be a teaching object within the classroom, so we propose, in the methodology, a didactic sequence with the intention of working in a planned way all the stages that make up the studied genre. In order to reach our objective, we have searched for a bibliographic reference mainly in the studies of: Antunes (2003, 2009), Bakhtin (1997), Blikstein (2016), Dolz and Schneuwly (2011), Ferreira (2010) and Ribeiro (2009). Also important were the contributions of the National Curricular